Compreendendo a dinâmica familiar de adolescentes expostos a violência sexual intrafamiliar - Favaretto, Priscila Zanardi [UNESP]; Valle, Tânia Gracy Martins do [UNESP] (My University, 2011)
Violence in adolescence, specifically sexual violence, is a topic of great relevance. Not only in Brazil but the world has witnessed the increase of sexual violence, becoming the most prevalent morbid occurrence in adolescence. Draws attention to the phenomenon of sexual violence against children and adolescents not only the fact that most of the victims are assaulted in their own home environment, but also the type of relationship between victim and aggressor. Thus, based on systemic approach, this study aimed to compose eend family dynamics of adolescent victims of sexual intra-familial. Participants were seven teenagers and their parents, users and beneficiaries of services offered by CREAS - Reference Center for Specialized Social Assistance in a municipality of Mato Grosso do Sul. The instruments used were the Test of Drawing in Colour of the Family (FCDT) and a questionnaire about the pictures taken and family interactions. The results indicated the difficulty in differentiating family roles, especially regarding the differentiation of the mother and daughter, a fact that seemed to be the motivator for the impoverishment of individuation in groups. Also noted the presence of conflict between the familiar figures probably originated from this abusive situation. In this context, the studied families showed communication difficulties between family members, hindering the integration between them, as well as the existence of an authoritarian leadership and strict rules performed by the father figure. These results may support preventive and therapeutic actions to situations of sexual violence against children and adolescents. Thus, it is suggested that psychological counseling for the study participants and other stakeholders with a view to reducing damage and recovery of quality of life for all family members, as well as the need for further studies in the area in question.

A violência na adolescência, mais especificamente a violência sexual, é um tema de grande relevância na atualidade. Mundialmente tem-se presenciado o aumento da violência sexual, transformando-se na ocorrência mórbida de maior prevalência na adolescência. Chama atenção no fenômeno da violência sexual contra crianças e adolescentes não somente o fato de a maior parte das vítimas serem agredidas no próprio ambiente familiar, mas também o tipo de vínculo entre vítima e agressor. Dessa forma, baseado na abordagem sistêmica, este estudo objetivou compreender a dinâmica familiar de adolescentes vítimas de violência sexual intrafamiliar. Participaram do estudo sete adolescentes e seus respectivos pais, usuários e beneficiários dos serviços ofertados pelo CREAS – Centro de Referência Especializado da Assistência Social de um município do Estado do Mato Grosso do Sul. Os instrumentos utilizados foram o Teste do Desenho em Cores da Família (TDCF) e um questionário a respeito das figuras realizadas e das interações familiares. Os resultados indicaram a dificuldade na diferenciação dos papéis familiares, principalmente no que tange a diferenciação da díade mãe e filha, fato que pareceu ser o motivador para o empobrecimento da individuação nos grupos. Também percebeu-se a presença de conflitos entre as figuras familiares, provavelmente advindos da situação abusiva presente. Neste contexto, as famílias estudadas demonstraram dificuldades de comunicação entre os membros familiares, prejudicando a integração entre eles, bem como a existência de uma liderança autoritária e regras rígidas desempenhadas pela figura paterna. Tais resultados podem subsidiar ações preventivas e terapêuticas para situações de violência sexual contra crianças e adolescentes. Dessa forma, sugere-se o acompanhamento psicológico para os participantes deste estudo e demais envolvidos, com vistas à redução dos danos causados e a recuperação da qualidade de vida para todos os membros da família, assim como a necessidade de continuidade de estudos na área em questão.
Understanding the family dynamics of adolescents exposed to sexual violence
Keywords: Sexual violence; Adolescents; Family dynamics; Family colored drawing test; Violência sexual; Adolescência; Dinâmica familiar; Teste do desenho em cores da família